Essentials of genetics - Klug, William S.; Cummings, Michael R.; Spencer, Charlotte A.; Palladino, Michael Angelo; Killian, Darrell (Harlow Essex, UK Pearson, 2021)
Known for its focus on conceptual understanding, problem solving, and practical applications, the bestselling Essentials of Genetics strengthens problem-solving skills and explores the essential genetics topics that today’s students need to understand. The 10th Edition has been extensively updated to provide comprehensive coverage of important, emerging topics such as CRISPR-Cas, epigenetics, and genetic testing. Additionally, a new Special Topics chapter covers Advances in Neurogenetics with a focus on Huntington Disease, and new essays on Genetics, Ethics, and Society emphasise ethical considerations that genetics is bringing into everyday life.--Provided by publisher.
Introduction to genetics -- Mitosis and meiosis -- Mendelian genetics -- Modification of mendelian ratios -- Sex determination and sex chromosomes -- Chromosome mutations : variation in number and arrangement -- Linkage and chromosome mapping in eukaryotes -- Genetic analysis and mapping in bacteria and bacteriophages -- DNA structure and analysis -- DNA replication -- Chromosome structure and DNA sequence organization -- The genetic code and transcription -- Translation and proteins -- Gene mutation, DNA repair, and transposition -- Regulation of gene expression in bacteria -- Regulation of gene expression in eukariotes -- Recombinant DNA technology -- Genomics, bioinformatics, and proteomics -- The genetics of cancer -- Quantitative genetics and multifactorial traits -- Population and evolutionary genetics.
Authorized adaptation from the United States edition, entitled: Essentials of genetics / by William S. Klug, Micahel R. Cummings, Charlotte A. Spencer, Michael A. Paalladino and Darrell J. Killian -- Tenth edition. 2020.
Keywords: Genetic Phenomena